Animated Video as History Learning Media: Representing Martha Christina Tiahahu in Senior High School in Malang - Maulidda Famairisa (Criksetra: Jurnal Pendidikan Sejarah, 2026)
This study highlights the importance of using innovative learning media in education, particularly in history lessons. Using the ADDIE R&D model, the study aims to produce animated video media about Martha Christina Tiahahu for grade XI at Senior High School No. 1 in Tumpang Malang, developed with the Animaker platform. In addition, this study also evaluates the validity of the media through trials by material and media experts and measures the feasibility of the resulting media. Data were obtained through observation, interviews, and questionnaires with analysis using a Likert scale. The results show that the media validity reached 90% from media experts and 95% from material experts, with the criteria of "Very Valid". In a field test involving 35 students, 88% were obtained in a small trial and 89% in a large trial, indicating the media is classified as "Very Feasible". The findings show that the use of animated videos is able to attract students' attention and create a pleasant classroom atmosphere, making this media very valid and appropriate for the history learning process.